Impact of industrial pollution on physiological growth and nutrient contents of common green leafy vegetables - V, Tharani; P, Revathi (Kongunadu Research Journal, 2020)
The agriculture has been always remaining as backbone of economy. Maintenance of soil and water quality has been pointed out as one of the major contributing factors for sustainability of agricultural production. Conserving the water sources and agricultural lands for getting non-toxic food from plants, the present study has undertaken to investigate the mineral composition and vitamin contents of green leafy vegetables as well as the effect of pollution on plant physiology. Normal soil and water, Industrial non - recycled water and soil were collected from the Thekkampatti village of Karamadai, Coimbatore district, Tamil Nadu. Industrial recycled water and soil have collected from the Otterpalayam (Annur) of Coimbatore district, Tamil Nadu. The result indicates that industrial non recycled water possess pH of 8.9 shows alkalinity. Industrial water non recycled soil the Chromium (58.0 mg/L) is present in higher quantity. The germination percentage was desirably good in normal soil and followed by water recycled soil cultivated green leaves.The impact of pollution present in the non-recycled soil was clearly observed in respective plant leaf numbers, size and shoot length. The present study is also one of the attempts to prove the importance of recycling of industrial pollution as well as the impact of non-recycled heavy metal pollution in common green leafy vegetables growth and nutrients. The industries should follow the recycling process based on the chemicals utilized for their products. The soil and water are need to conserve with efficient recycling methods in order to prevent the pollution which in turn becomes health hazards for the human and other living organisms through crop plants.